2006
DOI: 10.1103/physreve.74.050101
|View full text |Cite
|
Sign up to set email alerts
|

Metastability, nucleation, and noise-enhanced stabilization out of equilibrium

Abstract: We study metastability and nucleation in a kinetic two-dimensional Ising model that is driven out of equilibrium by a small random perturbation of the usual dynamics at temperature T. We show that, at a mesoscopic/cluster level, a nonequilibrium potential describes in a simple way metastable states and their decay. We thus predict noise-enhanced stability of the metastable phase and resonant propagation of domain walls at low T. This follows from the nonlinear interplay between thermal and nonequilibrium fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Several theoretical studies have shown that the average escape time from metastable states in the presence of fluctuating and static potentials is characterized by nonmonotonical behavior with respect to the noise intensity [14,23,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This resonance-like behavior, called noise enhanced stability (NES), is in contrast with the monotonic behavior predicted by Kramers theory [68,69]: the stability of metastable or unstable states is in fact enhanced by the noise with the average lifetime resulting larger than the deterministic one.…”
Section: Introductionmentioning
confidence: 46%
“…Several theoretical studies have shown that the average escape time from metastable states in the presence of fluctuating and static potentials is characterized by nonmonotonical behavior with respect to the noise intensity [14,23,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This resonance-like behavior, called noise enhanced stability (NES), is in contrast with the monotonic behavior predicted by Kramers theory [68,69]: the stability of metastable or unstable states is in fact enhanced by the noise with the average lifetime resulting larger than the deterministic one.…”
Section: Introductionmentioning
confidence: 46%
“…The data obtained for i 0 = 0.5, shown in (a) of Figure 4, as the noise intensity increases, exhibit an effect of noise-enhanced stability (NES) [42,43,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], a noise-induced phenomenon consisting of a nonmonotonic behavior with the appearance of a maximum. In the presence of NES, the stability of metastable states is enhanced, and the average lifetime of the metastable state increases non-monotonically with the noise intensity.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17]), which means that the Brownian particle will be trapped into the metastable state in the limit of very small noise intensities; (b) a nonmonotonic behavior of the lifetime of the metastable state as a function of the noise intensity and as a function of the driving frequency of the fluctuating potential (see Ref [10]). Noise-enhanced stabilization out of equilibrium in a study of metastability and nucleation in a kinetic two-dimensional Ising model was recently predicted in Ref [18]. Moreover a nonmonotonic behavior of the mean first passage time (MFPT) of a Brownian colloidal particle in a symmetric fluctuating periodic spatial potential as a function of the oscillation period was revealed [21].…”
Section: Introductionmentioning
confidence: 99%
“…[18]). It was demonstrated that the metastable lifetimes for impurity-free kinetic Ising models exhibit system-size and field dependence.…”
Section: Ising Modelmentioning
confidence: 99%
See 1 more Smart Citation